Energy performance assessment in urban planning competitions. (1st October 2015) - Eicker, Ursula; Monien, Dirk; Duminil, Éric; Nouvel, Romain
Highlights: Quantification of energy efficiency in urban planning. Analysis based on 3D (city) model. Impact evaluation of urban form on energy demand, supply and building costs. Primary energy balance with and without inclusion of shadowing effects. Abstract: Many cities today are committed to increase the energy efficiency of buildings and the fraction of renewables especially in new urban developments. However, quantitative data on building energy performance as a function of urban density, building compactness and orientation, building use and supply options are rarely available during the design of new cities or early scenario analysis for existing city quarters, making it difficult for cities to effectively evaluate which concepts work today and in the future. The paper proposes a methodology to assess the energy demand and supply options as a function of the availability of geometry, building standard and use data. An automated procedure was implemented to identify each building's geometry and volume and transfer the information to a simulation tool, which then calculates heating demand and solar energy generation on roofs and facades. The simulation includes shading calculations for each segment of the façades and roofs and thus allows a very detailed quantification of the building energy demand. By applying the methodology to a case study city quarter designed in an urban competition in Munich, it could be shown how the urban design influences the energy demand of the quarter and which fractions of renewable energy can be integrated into the roofs. While the building insulation standard and use are the is most important criteria for building energy efficiency (with an impact of more than a factor 2), the exact geometrical form, compactness and urban shading effects influences the energy demand by 10–20%. On the other hand, the detailed roof geometry and orientation influences the possible solar coverage of electricity or thermal needs. Zero energy city quarters with solar resources alone are only possible when all available building surface areas are fully optimized and do not need to fulfill other requirements such as providing roof gardens, terraces or others. Combinations with other more centralized renewable resources such as deep geothermal, solar or biomass heat or cogeneration plants are often necessary to achieve zero energy balances.